Pengaruh Motivasi Kerja, Disiplin, dan Budaya Organisasi Terhadap Kinerja Pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Pesawaran - Muhammad Galih Dharmawan; Agus Purnomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of work motivation, work discipline, and organizational culture on employee performance using the grand theory of Ability–Motivation–Opportunity (AMO). The AMO theory emphasizes that performance is determined by individual motivation, the ability to carry out tasks, and the opportunities created by the organization. The problem addressed is the suboptimal employee performance, making it necessary to empirically test the role of these three factors. This research provides empirical evidence of the relationship between those variables and performance. The study employs a quantitative approach using multiple linear regression analysis based on questionnaire data collected from employees. Testing is conducted through the t-test to examine partial effects and the F-test to examine simultaneous effects. The model is also tested using classical assumption tests to ensure the validity of the analysis. The results are used to explain the strength of the influence of each variable. The findings show that work motivation and work discipline have a positive and significant effect on employee performance. Organizational culture has the most dominant positive and significant influence in improving performance. Simultaneously, all three variables have a positive and significant effect on employee performance. These results support the AMO framework that the combination of motivation, ability, and opportunity produces optimal performance. The implication is that performance improvement must be carried out integratively through strengthening motivation, enforcing discipline, and developing a supportive organizational culture. Organizations need to create systems that enable employees to be capable and have the opportunity to demonstrate their best performance. An AMO-based approach makes human resource management more focused and sustainable. Ultimately, this leads to improved performance and better public service quality.